KEANEKARAGAMAN DAN KOMPOSISI KEONG AIR TAWAR (MOLLUSCA: GASTROPODA) DI BEBERAPA SITU KABUPATEN BOGOR DAN KABUPATEN SUKABUMI - Mujiono, Nova; Afriansyah, Afriansyah; Putera, Alexander KS; Atmowidi, Tri; Priawandiputra, Windra (LIMNOTEK - Perairan Darat Tropis di Indonesia, 2019)
Many small lakes in Bogor and surrounding areas continue to shrink by silting and land conversion that will affect the diversity of aquatic fauna species, including freshwater snails. Research on the diversity and distribution of freshwater snails was conducted in Bogor Regency (Situ Cilalay, Situ Ciriung, Situ Kabantenan) and Sukabumi (Situ Gunung) in September-November 2017. This study identified freshwater snail species, analyzed the similarity of species composition and distribution, and analyzed the influencing environmental factors. Snail sampling from each lake was carried out at three stations using 5 x 1 m2 plots. A total of 936 individual specimens from 12 stations have been collected and identified, consisting of 7 families and 12 species of freshwater snails. Filopaludina javanica dominates the population in Situ Cilalay, Situ Ciriung, and Situ Kabantenan with the presence of 417 individuals (44.5%), while Melanoides tuberculata is the most widely distributed species found in 11 of 12 stations. The presence of two species, Clea sp. found in Situ Cilalay and Polypylis kennardi found in Situ Ciriung and Situ Kabantenan, has not been reported previously.